Strategi dakwah Nabi Muhammad SAW pada periode Makkah dan implikasinya dengan dakwah kontemporer - Harsono, Karima Audy Augustine (Maliki Interdisciplinary Journal, 2026)
An important historical paradigm for ideological growth and organisational endurance is the Makkah era (610–622 CE). The strategic transition of Prophet Muhammad from covert to open Da'wah is examined in this paper, along with its applicability to current issues. Using a historical approach that focusses on heuristic, critique, interpretation, and history, the study discovers that Tauhid and extensive personal character development (tarbiyah) are the main tactics. This strategy produced As-Sabiqunal Awwalun, a strong core group that was able to resist persecution. This article makes the case that the Prophet's adaptable approach, which is based on fiqh al-aulawiyat (priority setting), provides a strong framework for putting creed (akidah) and moral instruction ahead of short-term political objectives in contemporary Islamic advocacy. The Makkah model is still a crucial tactical manual for negotiating pluralistic communities today.